Multi-omic analysis on the molecular mechanisms of rapid growth in ‘Deqin’ alfalfa after space mutagenesis - Qian Kuang; Chenggang He; Heping Huang; Hua Jiang (BMC Plant Biology)
Abstract Background Space-induced plant mutagenesis, driven by cosmic radiation, offers a promising approach for the selective breeding of new plant varieties. By leveraging the unique environment of outer space, we successfully induced mutagenesis in ‘Deqin’ alfalfa and obtained a fast-growing mutant. However, the molecular mechanisms underlying its rapid growth remain poorly unexplored. Results Comparative analyses of transcriptomics, proteomics, and hormone profiles were conducted in root, stem, and leaf tissues of both mutant and non-mutagenic materials. Targeted plant hormone showed notable increases in the levels of 3-indolebutyric, indole-3-acetic, and 3-indolepropionic acids in the mutant, with percentage increases of 33.55%, 32.49%, and 30.39%, respectively. Zeatin-riboside and dihydrozeatin riboside levels increased by 164.92% and 25.86%, while giberellin (GA) 7, GA3, and GA1 levels increased by 219.52%, 68.74%, and 40.98%. Non-mutagenic materials sprayed with exogenous 3-indolebutyric acid, zeatin-riboside, and GA7 exhibited significant growth acceleration. Transcriptomics identified 49,095 annotated genes, with 2,009, 1,889, and 1,760 upregulated and 2,082, 2,035, and 1,499 downregulated in the leaves, stems, and roots, respectively. Twenty-two genes related to plant hormone biosynthesis showed significant alterations. Screening through weighted correlation network analysis revealed ten candidate genes, four of which were associated with photosynthesis and starch and sucrose metabolism. Integrated analysis of targeted plant hormone metabolomics and transcriptomics indicated that plant hormone signal transduction played a crucial role. Proteomics revealed 479 differentially accumulated proteins, of which 174 were upregulated and 305 were downregulated. Integrated proteomics and transcriptomics showed that photosynthesis, starch and sucrose metabolism, carbon metabolism, and carbon fixation in photosynthetic organisms promoted the rapid growth of the mutants. By integrating multi-omics data, we elucidated the synergistic effects of pathways such as hormone signal transduction and tryptophan metabolism on the rapid growth of the mutants. Conclusion This study demonstrated the significance of plant hormones in the rapid growth of the mutants and identified key genes and metabolic pathways. Our findings provide valuable information for the genetic improvement of alfalfa varieties and serve as a reference for achieving rapid growth in other plants.